Pelatihan Video Editing di SMK Muhammadiyah 1 Palembang - Bobby Halim; Husni Mubarat; Herdy Kurniawan; Muhammad Rivan Hakim (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Video Editing Training at SMK Muhammadiyah 1 Palembang is a community service program aimed at enhancing students' skills in video editing using Adobe Premiere Pro. This training was conducted in response to the rapid development of digital technology and the increasing demand for creative industry professionals in the Industry 5.0 era. The methods applied in this training included observation, interviews, teaching, demonstrations, technology-based learning, and evaluation. The results indicate an improvement in participants' understanding and technical skills in video editing, including selecting appropriate software and implementing digital marketing strategies through video content. Additionally, participants gained entrepreneurial insights relevant to current creative industry trends. This program is expected to equip SMK Muhammadiyah 1 Palembang graduates with competitive skills in the workforce, particularly in multimedia and digital content production. Training evaluations show that the applied learning methods effectively enhance participants' competencies. In the future, similar programs should be expanded with broader coverage and collaboration with various stakeholders to support the advancement of the creative industry ecosystem.